ANALISIS PENGUKURAN KINERJA PERUSAHAAN MENGGUNAKAN PERSPEKTIF KEUANGAN, PERSPEKTIF PELANGGAN, PERSPEKTIF PROSES BISNIS INTERNAL DAN PERSPEKTIF PERTUMBUHAN PEMBELAJARAN (BALANCE SCORE CARD) - Nurul Annisa (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to determine the performance of PT. Gapura Angkasa Yogyakarta viewed from a financial perspective, to know the performance of PT. Gapura Angkasa Yogyakarta viewed from a financial perspective, to know the performance of PT. Gapura Angkasa Yogyakarta viewed from the perspective of internal business processes, and to determine the performance of PT. Gapura Angkasa Yogyakarta viewed from the perspective of growth and learning. The type of this research is quantitative descriptive research. The population used are some customers and employees who work in PT. Gapura Angkasa Yogyakatya. Sampling method used using proportional stratified random sampling. The type of data used is quantitative and qualitative data. Then the data source used in the form of primary and secondary data. The results of the research indicate that the financial performance of PT. Gapura Angkasa Yogyakarta is quite good and has been pressing costs to reduce expenditure. This is also accompanied by good earnings achievement. the result from the customer perspective is said to be well indicated from the level of satisfaction of the average customer is satisfied with the condition of service, from the perspective of growth and learning is shown from the index of employee satisfaction reached 972 points or are in 756-1.092 point intervals or categorized not satisfied. Keywords: financial perspective, customer perspective, internal business process perspective, and learning growth perspective.